2012
DOI: 10.18632/oncotarget.623
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-Phosphate Dehydrogenase: A Promising Target for Molecular Therapy in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most highly lethal malignancies ranking as the third leading-cause of cancer-related death worldwide. Although surgical resection and transplantation are effective curative therapies, very few patients qualify for such treatments due to the advanced stage of the disease at diagnosis. In this context, loco-regional therapies provide a viable therapeutic alternative with minimal systemic toxicity. However, as chemoresistance and tumor recurrence negatively impact the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 80 publications
1
61
0
Order By: Relevance
“…Non-tumour cells are expected to be less sensitive to glycolysis inhibition than malignant cells, which are more dependent on this pathway to generate ATP and proliferate [34]. Therefore, GAPDH emerges as a promising therapeutic target against cancer since it is overexpressed in 21 cancer classes [3] and involved not only in cell proliferation and glycolysis but also in several other mechanisms which are upregulated in tumour cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Non-tumour cells are expected to be less sensitive to glycolysis inhibition than malignant cells, which are more dependent on this pathway to generate ATP and proliferate [34]. Therefore, GAPDH emerges as a promising therapeutic target against cancer since it is overexpressed in 21 cancer classes [3] and involved not only in cell proliferation and glycolysis but also in several other mechanisms which are upregulated in tumour cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to deactivate GAPDH was first described in the year 1993 and autographic evidence was provided in 2010 [49,50]. As a multifunctional enzyme that is often upregulated in cancer cells, GAPDH is reported to support tumorigenesis and chemoresistance and therefore constitutes a promising target for antitumoral therapy [51,52].…”
Section: Targeting Cancer Metabolismmentioning
confidence: 99%
“…Separate studies even suggested that GAPDH expression was correlated with chemotherapy-induced DNA damage response in vitro [12][13][14]. A study even suggested the heavily regulation of GAPDH during HCC carcinogenesis and progression in patients with HBV related HCC [15], as it can affect the proliferative potential of cancer cells in HCC [16]. HBV infection, the presence of cirrhosis and male gender are repeatedly recognized as the independent risk factors for the development of HCC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%